Opportunistic colonizers in the Kallankurichchi Formation, Cauvery Basin, South India: Implications on Maastrichtian environmental stress. (5th December 2020) - Muthuvairavasamy, Ramkumar; Siddiqui, Numair Ahmed; Rai, Jyotsana; Desai, Bhawanisingh G.; Menier, David
Abstract : Serpulids are marine filter‐feeding annelids that live in calcareous tubes. Their distribution, colonization, and proliferation are dependent on physical environmental variables, including energy conditions. This article documents the occurrences of serpulid colonies over opportunistic colonizing trace fossil of Ophiomorpha ‐rich sedimentary unit in the Lower Maastrichtian Kallankurichchi Formation of the Ariyalur Group, Cauvery Basin, South India and links them with ecosystem dynamics, as a function of changes in eustatic and other relative sea‐level changes and attendant variations in environmental parameters. Present observations indicate episodic changes in faunal composition, diversity, and population, across the boundary between Kattupiringiyam Inoceramus limestone Member and Tancem biostromal Member of the Kallankurichchi Formation. The boundary marked a significant change from low‐moderate energy, to high‐energy waters, thus replacing a filter‐feeding community by an opportunistic community. The opportunistic colonizers/trace makers of Ophiomorpha irregulaire occupied the ecospaces vacated by the sea‐level changes. Systematic studies of faunal association across the boundary indicate a sudden appearance of significant populations of Serpula colonies above the surface (i.e., after the changes in ecosystem conditions) and enhancement of intensity of sponge boring in benthic organisms. This means that the changes brought about by the newer environmental conditions were supportive for opportunistic colonizers followed by parasitic and commensalic organisms. Significant reduction of Gryphaea population that was increasingly replaced by Alectryonia, Exogyra, and Terebratula is also documented. These changes, collectively, indicate prevalent environmental stress due to relative sea‐level variations and attendant ecological conditions, to which, the opportunistic colonizers and parasitic organisms responded positively, while the native organisms dwindled in population and were forced to parasitic invasions. Abstract : Inferred geological events and stratigraphic variations of faunal community structure, associations, life‐style relationships The facies characteristics and contact relationships between various facies types, biological and other sedimentary structures, major fossil community occurrence, association, diversification, dwindling, interactions among fossil community as observable in the field and laboratory.